2022
DOI: 10.1021/acsptsci.2c00045
|View full text |Cite
|
Sign up to set email alerts
|

Different Aspects of Emetine’s Capabilities as a Highly Potent SARS-CoV-2 Inhibitor against COVID-19

Abstract: In the global movement to find the appropriate agents to fight the coronavirus disease of 2019 (COVID-19), emetine is one of the strongest anti-SARS-CoV-2 compounds with sub-micromolar EC 50 values, identified in several studies and high-throughput screening efforts. The reported anti-SARS-CoV-2 mechanisms indicate the effect of this compound on both virus-based and host-based targets. In addition to having excellent antiviral effects, emetine can relieve COVID-19 patients by reducing in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 112 publications
0
28
0
Order By: Relevance
“…There are also studies showing that the synergy between remdesivir and emetine can inhibit viral growth ( 87 ). Studies have found that emetine not only has a certain antiviral effect, but also can reduce the inflammatory response of patients by inhibiting the activity of NF-κB through IκBα phosphorylation, and can also reduce pulmonary hypertension by regulating various cellular processes ( 88 ). Progesterone is a sex hormone, and it also has some anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies showing that the synergy between remdesivir and emetine can inhibit viral growth ( 87 ). Studies have found that emetine not only has a certain antiviral effect, but also can reduce the inflammatory response of patients by inhibiting the activity of NF-κB through IκBα phosphorylation, and can also reduce pulmonary hypertension by regulating various cellular processes ( 88 ). Progesterone is a sex hormone, and it also has some anti-inflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“… 568 , 569 Hence, emetine can be used as a lead compound to design high-safety antiviral drugs in the future. 570 Cepharanthine is a bisbenzylisoquinoline alkaloid from tubers of Stephania , which is used as an alopecia drug in Japan. 571 Its antiviral ability has been verified in vitro against HIV, human T-lymphotropic virus type 1 (HTLV-1), HBV, SARS-CoV, and HCoV-OC43.…”
Section: Structures Of Small Molecule Drugs For Covid-19 Therapymentioning
confidence: 99%
“…Its effect against other coronaviruses is well documented and SARS-CoV-2 is no exception. Several papers have documented the multifaceted approach of emetine against SARS-CoV-2, inhibiting not only viral entry, but also replication and proliferation [ 164 ]. In a study published by Wang et al (2020) emetine swiftly reduced viral activity in SARS-CoV-2 infected Vero cells and blocked viral entry in pretreated cells [ 178 ].…”
Section: Medicinal Plant-produced Metabolites (Small Molecules) Again...mentioning
confidence: 99%